INTEGRATING ONE OF INTERNAL STRUCTURE OF DISCOURSE CALLED ‘PROCESS’ IN WRITING PROCEDURE TEXT FOR INTERMEDIATE LEVEL - Emilia Widuri (Prasasti: Journal of Linguistics)
In this article the researcher applies one of internal structure of discourse called ‘Process’ in writing ‘Procedures text’. Procedure text is a piece of writing that tells us information of making/doing something through several steps/directions. There are two important parts that students have to consider in procedure text; the generic structure and the language features. In the language features, the internal structure of “Process” of discourse integrated. The aim of internal structure of “Process” are offers the procedure/process for how something is done/created. The problem occurs when students ignore the internal structure of discourse, therefore they will face difficulties in writing process.